Differential Modulation of Mouse Heart Gene Expression by Infection With Two Trypanosoma cruzi Strains: A Transcriptome Analysis - Castro, Tiago Bruno Rezende de; Canesso, Maria Cecilia Campos; Boroni, Mariana; Chame, Daniela Ferreira; Souza, Daniela de Laet; Toledo, Nayara Evelin de; Tahara, Eric Birelli; Pena, Sergio Danilo; Machado, Carlos Renato; Chiari, Egler; Macedo, Andrea; Franco, Gloria Regina (Frontiers in Genetics, 2020)
The protozoan Trypanosoma cruzi (T. cruzi) is a well-adapted parasite to mammalian hosts and the pathogen of Chagas disease in humans. As both host and T. cruzi are highly genetically diverse, many variables come into play during infection, making disease outcomes difficult to predict. One important challenge in the field of Chagas disease research is determining the main factors leading to parasite establishment in the chronic stage in some organs, mainly the heart and/or digestive system. Our group previously showed that distinct strains of T. cruzi (JG and Col1.7G2) acquired differential tissue distribution in the chronic stage in dually infected BALB/c mice. To investigate changes in the host triggered by the two distinct T. cruzi strains, we assessed the gene expression profiles of BALB/c mouse hearts infected with either JG, Col1.7G2 or an equivalent mixture of both parasites during the initial phase of infection. This study demonstrates the clear differences in modulation of host gene expression by both parasites. Col1.7G2 strongly activated Th1-polarized immune signature genes, whereas JG caused only minor activation of the host immune response. Moreover, JG strongly reduced the expression of genes encoding ribosomal proteins and mitochondrial proteins related to the electron transport chain. Interestingly, the evaluation of gene expression in mice inoculated with a mixture of the parasites produced expression profiles with both up- and downregulated genes, indicating the coexistence of both parasite strains in the heart during the acute phase. This study suggests that different strains of T. cruzi may be distinguished by their efficiency in activating the immune system, modulating host energy metabolism and reactive oxygen species production and decreasing protein synthesis during early infection, which may be crucial for parasite persistence in specific organs.